The Kura-Araxes ‘expansion’: A climate change-related phenomenon? - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Two of the documented global climate changes of the Holocene that are known in the academic literature as the ‘5.2 ka BP’ and ‘4.2 ka BP’ events, coincide with two important stages of the Early Bronze Age Kura-Araxes culture of Armenia. The ‘4.2 ka BP event’ coincides with the final stage of this culture, the process of fragmentation and decline observed for the Kura-Araxes from 2500 BC onwards. It ends at around 2200 BC with abandonment or destruction of the Kura-Araxes settlements, accompanied by increased population shifts that led to almost total desertion of large areas both in the Kura-Araxes interfluve, the ‘homeland’ of this culture, and elsewhere. In parallel, this process was accompanied by migrations of new population groups (the influx of the bearers of the ‘Kurgan culture’ into the highland). The second phenomenon is the so-called ‘Kura-Araxes expansion’ which took place some hundred years prior. The dating of the ‘expansion’ at around 3000-2900 BC shows that it took place in another period of drastic climate change. The manifestations of the societal crisis observed in the Kura-Araxes cultural world, the increased mobility of the population and the movements (‘expansion’) to more favourable areas may indicate that we are dealing with interrelated phenomena.